The devaluation of female labour in fruit and vegetable packaging plants in Spanish Mediterranean agriculture. (March 2020) - de Castro, Carlos; Reigada, Alicia; Gadea, Elena
Based on the evidence found in two case studies of intensive agriculture in Southern Spain, this article analyses the impact of business strategies aimed at devaluing packaging plant work in the competitive integration processes currently taking place in the global agri-food value chain. The article explores three business strategies: the feminisation, segmentation and deskilling of labour, along with ethnic substitution and labour recruitment outsourcing mechanisms. Although it acknowledges the importance of the dynamics of global competition, the article focuses mainly on how firms articulate their strategies in packaging plants within the political, family and sociocultural frameworks of specific local contexts. The analysis uses a qualitative methodology based on in-depth interviews and participant observations.